Top five [videorecording (DVD)] - Rock, Chris; Rock, Chris; Dawson, Rosario; Union, Gabrielle; Hart, Kevin, 1979-; Morgan, Tracy, 1968-
A comedian tries to change his tune and become a serious actor. His fiance eventually convinces him to air their wedding on television as a reality-TV show. An encounter with a journalist forces him to confront the comedy career, and the past, that he's left behind.